Top 100 cited articles on hemodialysis: A bibliometric analysis. Issue 38 (24th September 2021) - Lee, Yoo Jin; Heo, Chang Min; Park, Sihyung; Kim, Yang Wook; Park, Jin Han; Kim, Il Hwan; Ko, Junghae; Park, Bong Soo
Abstract: Introduction: This study was conducted to better understand hemodialysis by reviewing the most-cited articles related to it. Methods: We searched articles on the Web of Science and selected the 100 most frequently cited articles. Subsequently, we reviewed these articles and identified their characteristics. Results: The 100 most frequently cited articles were published in 21 journals. The majority of these papers were published in the following journals: Kidney International (26 articles), New England Journal of Medicine (18 articles), Journal of the American Society of Nephrology (14 articles), and the American Journal of Kidney Disease (13 articles). The 100 most-cited articles were published in 25 countries. The United States of America was the country with the highest number of publications (65 articles). The University of Michigan was the institution with the highest number of articles (14 articles). FK Port was the author with the largest number of publications (13 articles). Conclusions: This is the first study in the field of nephrology that provides a list of the 100 most-cited articles on hemodialysis. Through this study, clinicians will be able to recognize major academic interests and research trends in hemodialysis.